Key considerations based on pharmacokinetic/pharmacodynamic in the design of antibody-drug conjugates - Gao, Yangyang; Xia, Yuwei; Chen, Yixin; Zhou, Shiqi; Fang, Yingying; Yu, Jieru; Zhang, Leyin; Sun, Leitao (Frontiers in Oncology, 2025)
BackgroundAntibody-drug conjugate (ADC) is an anticancer drug that links toxins to specifically targeted antibodies via linkers, offering the advantages of high target specificity and high cytotoxicity. However, complexity of its structural composition poses a greater difficulty for drug design studies.ObjectivesPharmacokinetic/pharmacodynamic (PK/PD) based consideration of ADCs has increasingly become a hot research topic for optimal drug design in recent years, providing possible ideas for obtaining ADCs with desirable properties.MethodsFrom the assessment of the ADC action process based on PK/PD, we introduce the main research strategies of ADCs. In addition, we investigated the strategies to solve the prominent problems of ADC in the clinic in recent years, and summarized and evaluated the specific ways to optimize various problems of ADC based on the PK/PD model from two perspectives of optimizing the structure and properties of the drugs themselves. Through the selection of target antigen, the optimization of the linker, the optimization of novel small molecule toxins as payload, the optimization of ADC, overcoming the multi-drug resistance of ADC, improving the ADC tumor penetration of ADC, surface modification of ADC and surface bystander effect of ADC provide a more comprehensive and accurate framework for designing new ADCs.ResultsWe’ve expounded comprehensively on applying pharmacokinetics or pharmacodynamics while designing ADC to obtain higher efficacy and fewer side effects. From the ADC’s PK/PD property while coming into play in vivo and the PK/PD study strategy, to specific ADC optimization methods and recommendations based on PK/PD, it has been study-approved that the PK/PD properties exert a subtle role in the development of ADC, whether in preclinical trials or clinical promotion.ConclusionThe study of PK/PD unfolds the detailed mechanism of ADC action, making it easier to control related parameters in the process of designing ADC, limited efficacy and inevitable off-target toxicity remain a challenging bottleneck.